The Prolanis Gymnastic Intervention and Autogenic Relaxation on Blood Sugar Levels and Stress Levels Among Type 2 Diabetes Mellitus Patients - Nur Rezki; Rumahorbo, Hotma; Arwani; Pujiastuti, Rr. Sri Endang (Alta Dharma Publisher, 2022)
Background: Hyperglycemia in people with diabetes mellitus can be motivated by stress factors which include physical, biological, psychological, and socio-cultural stress. The importance of the nurse's role in the implementation of diabetes mellitus management will be able to provide a reduction in stress levels and increase the ability of self-care in self-controlling blood sugar levels of diabetics. Non-pharmacological management such as prolanis gymnastic and autogenic relaxation can control blood sugar levels and stress levels in patients with type 2 diabetes mellitus. Objective: The study aims to determine the effectiveness of prolanis gymnastic and autogenic relaxation on fasting blood sugar levels and stress levels among type 2 diabetes mellitus patients. Design: Quasi Experiment study pretest and post-test with control group design were applied in this study. Result: Repeated Measure Anova test showed a significant difference with the mean fasting blood sugar level and stress level with p=value 0.000 (<0.05). Independent T-test showed a significant difference between intervention group and control group on fasting blood sugar levels and stress levels after post-test in the third week. The intervention group is better at lowering fasting blood sugar levels and stress levels than control group seen from the higher value difference. Conclusion: The conclusion of this study is prolanis gymnastic and autogenic relaxation three times a week for three weeks effectively reduces fasting blood sugar levels and stress levels in patients with type 2 diabetes mellitus. This study can be used for reference for future research, controlling the patient’s diet, lifestyle, etc, and longer duration of intervention, so that the result obtained are more valid Keywords: Prolanis gymnastic, autogenic relaxation, fasting blood sugar levels, stress levels, type 2 Diabetes Mellitus